Конфліктогенні та геополітичні наслідки змін в етнічному балансі країн та регіонів - Качан, Олег (Видавництво Львівської політехніки, 2011)
Розглянуто зміни в етнічному балансі країн та регіонів як конфліктогенний чинник умов, за яких ці зміни набувають конфліктного значення. Показано геополітичний вимір проблеми. The article examines changes in ethnic balance of countries and regions as conflict-inducing factor as well as conditions needed for this changes to acquire a conflict importance. Also the geopolitical dimension of the problem is considered.
Conflict-inducing and geopolitical consequences of shifts in ethnic balances of states and regions
Keywords: політична демографія; етнічний баланс; конфлікти; міжнародна стабільність; геополітика; political demography; ethnic balance; conflicts; international stability; geopolitics